Oxford handbook of paediatrics - Acerini, Carlo L.; McClure, Robert J.; Tasker, Robert C. [ (Robert Charles)] , 1958- (Oxford University Press, 2008)
This handbook covers all significant aspects of acute and chronic paediatrics. Areas such as neonatology, surgery, genetics and congenital malformations and child protection are covered in a user-friendly and succinct style.